Structural and ultrastructural characterization of male reproductive tracts and spermatozoa in fig wasps of the genus Pegoscapus (Hymenoptera, Chalcidoidea) - Fiorillo, Bruno Silva (2008)
The three Pegoscapus species present the same internal reproductive tract features comprising testes with a single testicular tubule, seminal vesicles, vasa deferentia, accessory glands and an ejaculatory duct. The seminal vesicle shows two morphologically distinct portions although they do not resemble the separate chambers found in other Chalcidoidea. The anterior portion of the seminal vesicle shows a prominent epithelium and stores the mature spermatozoa, while the posterior region is formed by a thicker muscular sheath that participates on ejaculation. The sexual maturation in Pegoscapus is achieved at emergence, when the testicular degeneration occurs. The spermatozoa of Pegoscapus reveal a basic structure similar to that of other Chalcidoidea. In Pegoscapus sp1. and Pegoscapus sp2. they present the same features, whereas Pegoscapus tonduzi comprises some different characteristics. It measures approximately 160 μm in Pegoscapus sp1. and Pegoscapus sp2., while in P. tonduzi the spermatozoa measure about 360 μm. The extracellular sheath thickness is another difference among the species. While Pegoscapus sp1. and Pegoscapus sp2. show a thick extracellular sheath, in P. tonduzi this sheath is very thin resulting in a large space intervening between the extracellular sheath and the nucleus. Despite these differences, the three species analyzed share some characteristics that allow the establishment of an identity to the spermatozoon of the genus Pegoscapus: the seminal vesicle not divided in chambers; the absence of acrosomal structures in the spermatozoa; the length of the extracellular sheath; the central microtubules being the firsts to terminate in the sequence of microtubular cutoff at the final axonemal portion.